FIELD-ION MICROSCOPE ATOM-PROBE ANALYSIS OF THE EFFECT OF RRA HEAT-TREATMENT ON THE MATRIX STRENGTHENING PRECIPITATES IN ALLOY AL-7150 - Warren, P; Grovenor, C; Crompton, J (1992)
The heat treatment of retrogression and re-ageing (RRA) has been applied to commercial alloy Al-7150 resulting in an improvement in the SCC resistance of material aged to peak strength. Transmission electron microscopy (TEM), field-ion microscopy/atom-probe (FIM/AP) analysis and position sensitive atom-probe (POSAP) analysis have been used to investigate the matrix precipitate composition during various stages of the RRA treatment as a preliminary part of a wider study of matrix and grain boundary chemistry. TEM confirmed that there was an overall increase in precipitate size with retrogression time. For material retrogressed at 180°C there was a change in a matrix precipitate appearance suggesting a change in precipitate type and/or chemistry. FIM/AP studies showed that RRA at 180°C caused a marked increase in the copper content of the mainly magnesium + zinc precipitates in agreement with the work of Brenner et al. [Surf. Sci. 246 (1991) 210]. The solute levels were found to be far from the equilibrium stoichiometry of MgZn2, there being more magnesium than zinc. Three-dimensional POSAP analysis gave information about the precipitate size and morphology not available from conventional FIM/AP analysis due to the lack of precipitate imaging contrast in the FIM. In addition, the composition of precipitates can be established including the Al content which is hard to determine using FIM/AP due to the small size of the precipitates. © 1992.